2018
DOI: 10.1016/j.redox.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ROS cause motor deficits induced by synaptic inactivity: Implications for synapse pruning

Abstract: Developmental synapse pruning refines burgeoning connectomes. The basic mechanisms of mitochondrial reactive oxygen species (ROS) production suggest they select inactive synapses for pruning: whether they do so is unknown. To begin to unravel whether mitochondrial ROS regulate pruning, we made the local consequences of neuromuscular junction (NMJ) pruning detectable as motor deficits by using disparate exogenous and endogenous models to induce synaptic inactivity en masse in developing Xenopus laevis tadpoles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 82 publications
(130 reference statements)
1
33
0
Order By: Relevance
“…Consistent with experimental data in skeletal muscle wherein contractile activity (i.e., exercise) decreases whereas inactivity increases mitochondrial O 2 .− /H 2 O 2 production . In addition, silencing NMJ activity with neurotoxins or endogenous synapse pruning cues increases mitochondrial (O 2 .− /H 2 O 2 ) in vivo . The above‐mentioned theoretical and experimental evidence strongly suggests that: mitochondrial O 2 .− /H 2 O 2 are endogenous synaptic activity sentinels.…”
Section: Mitochondrial Ros Are Endogenous Synaptic Activity Sentinelssupporting
confidence: 83%
“…Consistent with experimental data in skeletal muscle wherein contractile activity (i.e., exercise) decreases whereas inactivity increases mitochondrial O 2 .− /H 2 O 2 production . In addition, silencing NMJ activity with neurotoxins or endogenous synapse pruning cues increases mitochondrial (O 2 .− /H 2 O 2 ) in vivo . The above‐mentioned theoretical and experimental evidence strongly suggests that: mitochondrial O 2 .− /H 2 O 2 are endogenous synaptic activity sentinels.…”
Section: Mitochondrial Ros Are Endogenous Synaptic Activity Sentinelssupporting
confidence: 83%
“…Second is the proposed intervention for selective subcellular localization. Mitochondria are ROSproducing and primary oxidative stress-damaging organelles [17,39]. Clinical trial reported that CoQ10-targeted mitochondrial ROS therapy to reduce major adverse cardiovascular events, hospitalization rates, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are mainly produced by the Fenton reaction induced by iron overload after ICH, which occurs primarily in the mitochondria [13][14][15]. And the selective mitochondrial ROS scavengers are reported superior to nonselective ROS scavengers in the treatment of many redox diseases involving mitochondrial dysfunction [16][17][18]. Therefore, it is urgent to explore the protective effect of selective mitochondrial ROS scavenger on secondary injury of ICH.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, reversible subunit alpha oxidation had only been assessed by redox proteomics usually in either isolated mitochondria or disease models [131]. Intrigued by a possible physiological redox regulatory role, we asked whether the alpha subunit is reversibly oxidized in oocytes and zygotes from the key developmental model Xenopus laevis (X. laevis) [132][133][134]. We hypothesized that the alpha subunit would be reversibly oxidized in oocytes to prevent wasteful ATP hydrolysis [135], but that fertilization induced ADP may provide an instructive cue to relieve reversible thiol oxidation to initiate embryonic mitochondrial ATP synthesis [136].…”
Section: Click Pegylation Is a Useful Tool To Assess Protein Thiol Rementioning
confidence: 99%